(untitled) - Freedman, David (New York, 1994)
The subject of fantasy and skepticism for centuries-- from William James's mechanical bride to 2001's Hal to Star Wars' R2D2-- artificial intelligence has been limited to number-crunching computers that are"smart" only in highly specific domains like chess-- until now. "Brainmakers" is an eye-opening, mind-expanding, and mind-blowing journey through laboratories engaged in cutting-edge research into neuro-science and robotics.
Keywords: Artificial intelligence,Brain